Workload and the quality of nursing care in critically ill patients: a systematic review - Esquivel-Franco, C.G. (Revista de Ciencias Médicas Torreón, 2026)
Introduction: The Intensive Care Unit (ICU) is a highlycomplex environment that requires continuous andspecialized care, exposing nursing staff to a high workload.This overload may affect both the physical and mental healthof professionals, as well as the quality and safety of careprovided to critically ill patients.Objective: To evaluatewhether workload overload among nursing staff affects thequality of care for critically ill patients in intensive careunits.Methodology: A systematic literature review wasconducted following PRISMA guidelines. The search wascarried out between March and May 2022 in the PubMed,Google Scholar, SCIELO, LILACS, and ScienceDirectdatabases. Studies published between 2010 and 2022 inSpanish, English, and Portuguese, related to nursingworkload in adult ICUs, were included. After applyinginclusion and exclusion criteria, 16 articles were selected forthe final analysis. Methodological quality was assessedaccording to the hierarchy of evidence proposed by Stetler etal.Results: The analyzed studies show a significantassociation between nursing workload overload anddeterioration in the quality of care. A high workload wasassociated with increased healthcare-associated infections,eficiencia y calidad de las mismas, dado que por cadapaciente que sea asignado por una enfermera aumente elriesgo de mortalidad (Isabel et al., 2021; Mol et al., 2017).Por esta razón, el ámbito psicosocial influye de manerapositiva como negativa hacia la salud, el bienestar yrendimiento del enfermero(a), en los cuales se presentancomo exigencias psicológicas; ajuste entre las tareas y lostiempos laborales, familiares y sociales; control sobre eltrabajo; apoyo social e instrumental de compañeros ysuperiores; calidad de liderazgo; compensaciones del trabajo;y seguridad en el empleo. En cuanto a las demandas mentalesson una de las principales fuentes de carga mental, teniendoefectos perjudiciales para la salud de los trabajadores y parael logro de los objetivos de la organización (Ceballos-Vásquez et al., 2015).ventilator-associatedpneumonia,pressureinjuries,medication errors, and higher mortality. Instruments such asthe Nursing Activities Score (NAS) and the TherapeuticIntervention Scoring System (TISS) were the most frequentlyused to measure workload, demonstrating that higher scoresare associated with poorer clinical outcomes and reducedpatient safety.Conclusions: The available evidence confirmsthat excessive nursing workload negatively impacts thequality of care for critically ill patients. Insufficient staffinglevels and inadequate personnel distribution in the ICU arekey factors contributing to adverse events and increasedmortality. Adequate human resource planning andcontinuous workload monitoring are essential to ensure safe,effective, and high-quality care in the intensive care setting.